How job and family demands impact change in perceived stress: A dyadic study - Ewelina Smoktunowicz; Roman Cieślak (International Journal of Occupational Medicine and Environmental Health, 2018)
Objectives The aim of this two-wave study has been to test the spillover and crossover of job and family demands on changes in perceived stress at work and in the family. Specifically, we proposed that demands from one domain (work or family) spilled over to another domain through interrrole conflict (work–family/family–work conflict) and context-specific self-efficacy. Additionally, we hypothesized that changes in perceived stress were impacted not only by a person’s own demands through interrole conflict but also by the demands of one’s significant other, in the process of crossover.